Floral Pattern of Keratic Precipitates in Vitreoretinal Lymphoma on In Vivo Confocal Microscopy. (3rd April 2021) - Mahendradas, Padmamalini; Srinivasan, Thanemozhi; Kawali, Ankush; Venkatesh, Ramesh; Hazarika, Diganta; Patil, Shekar; Sanjay, Srinivasan; Shetty, Rohit
ABSTRACT: Purpose: To describe the morphological patterns of keratic precipitates (KPs) in vitreoretinal lymphoma (VRL) using in vivo confocal microscopy (IVCM). Methods: Six eyes of three biopsy-proven VRL patients were included. KPs were identified and analyzed on IVCM. Results: On examination, pigmented KPs in four eyes, white central KPs in two eyes and anterior chamber cells with flare in six eyes and pseudo hypopyon in one eye were identified. A typical floral pattern of KPs on IVCM was noted in all eyes. Three eyes each showed the complete and incomplete floral patterns, respectively. Resolution of KPs on IVCM was noted after chemotherapy. Conclusion: In addition to the routinely used clinical and imaging markers like the visual acuity, presence of lymphomatous cells in the vitreous and optical coherence tomography findings, the presence and appearance of KPs on IVCM can also be considered as a useful, diagnostic and treatment monitoring marker in VRL.